2005
DOI: 10.1038/sj.jcbfm.9600032
|View full text |Cite
|
Sign up to set email alerts
|

Association of 14-3-3γ and Phosphorylated Bad Attenuates Injury in Ischemic Astrocytes

Abstract: Our recent findings indicate an induced upregulation of 14-3-3gamma mRNA and protein in ischemic cortical astrocytes. Despite being brain-specific, the functional role of 14-3-3gamma in the brain still remains largely unknown. In this study, we show that among all the 14-3-3 isoforms, only the gamma isoform is inducible under ischemia in astrocytes. Furthermore, this upregulation of 14-3-3gamma may play a specific protective role in astrocytes under ischemia. Overexpression experiments and antisense treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 30 publications
4
58
0
1
Order By: Relevance
“…A Western blot analysis showed that the expression level of 14-3-3γ protein decreased (28.8%) in N2a/ Ngb-siRNA cells compared with N2a/vec cells ( Figure 3C). We further confirmed the protective role of 14-3-3γ from oxidative stress by transfecting 14-3-3γ plasmids [24] into N2a/ Ngb-siRNA cells. A WST-8 assay demonstrated that overexpression of 14-3-3γ in N2a/Ngb-siRNA cells significantly enhanced cell viability following treatment with 150 µmol/L of H 2 O 2 compared with vector controls ( Figure 3D).…”
Section: Resultssupporting
confidence: 56%
See 4 more Smart Citations
“…A Western blot analysis showed that the expression level of 14-3-3γ protein decreased (28.8%) in N2a/ Ngb-siRNA cells compared with N2a/vec cells ( Figure 3C). We further confirmed the protective role of 14-3-3γ from oxidative stress by transfecting 14-3-3γ plasmids [24] into N2a/ Ngb-siRNA cells. A WST-8 assay demonstrated that overexpression of 14-3-3γ in N2a/Ngb-siRNA cells significantly enhanced cell viability following treatment with 150 µmol/L of H 2 O 2 compared with vector controls ( Figure 3D).…”
Section: Resultssupporting
confidence: 56%
“…14-3-3 proteins exist predominantly in the brain and mediate essential apoptotic signaling pathways [28,29] . We have previously reported that 14-3-3γ is up-regulated and protects astrocytes from ischemia-induced apoptosis [24,25] . We compared the expression of 14-3-3γ transcripts ( Figure 3B) and proteins ( Figure 3C) in N2a/NgbsiRNA and N2a/vec cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations